Manejemen Baitul Mal wat Tamwil (BMT) dalam Tinjuan Maqashid Syariah Perspektif Ibnu Asyur (Studi Pada Pondok Pesantren DDI Mangkoso) - Ulfa Hidayati (ITB AAS INDONESIA Surakarta, 2023)
In the past, the DDI Mangkoso Islamic Boarding School had a number of shortcomings, mainly due to a lack of proper training and professionalism. To keep the BMT Al Ta'awun business running at full capacity. Managers of business entities must develop an ideal business investment plan. The BMT Al Ta'awun business unit needs to be managed effectively, efficiently and professionally to achieve this goal. However, the anticipated level of welfare must be re-evaluated by considering the maqashid syariah. The research used in this research is qualitative research. The research location was conducted at the DDI Mangkoso Islamic Boarding School, Barru Regency, South Sulawesi, Indonesia. This research was conducted through interviews with BMT At Ta'awun managers and management of Islamic boarding school business units which were thoroughly investigated. The role of BMT At Ta'awun in improving the welfare of supervisors at the DDI AD Mangkoso Islamic Boarding School is felt to be very helpful through the many teachers and coaches who are assisted through capital at BMT At Ta'awun. In addition, the management of BMT At At Ta'wun is relevant to Maqashid Syariah Perspective Ibn Asyur who applied the four characteristics of Maqashid Syari'ah Al 'Amah as well as the goals of maqashid Hashah (special purposes).